2019
DOI: 10.1002/nag.3020
|View full text |Cite
|
Sign up to set email alerts
|

Analytical modeling on consolidation of stiffened deep mixed column‐reinforced soft soil under embankment

Abstract: SummaryStiffened deep mixed (SDM) column is a new ground improvement technique to improve soft soil, which can be used to increase bearing capacity, reduce deformation, and enhance stability of soft soil. This technique has been successfully adopted to support the highway and railway embankments over soft soils in China and other countries. However, there have been limited investigations on its consolidation under embankment loading. This paper developed an analytical solution for the consolidation of embankme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…They concluded that the stone columns mainly affect the anterior drainage process of the composite foundation. Zhang et al 13 . and Ye et al 14 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…They concluded that the stone columns mainly affect the anterior drainage process of the composite foundation. Zhang et al 13 . and Ye et al 14 .…”
Section: Introductionmentioning
confidence: 98%
“…7 They concluded that the stone columns mainly affect the anterior drainage process of the composite foundation. Zhang et al 13 and Ye et al 14 presented analytical solutions for the consolidation of a doublelayered foundation improved by deep mixed columns. Zhang et al 15 developed the consolidation solutions of the foundation partially penetrated with short deep mixed columns and long prefabricated vertical drains based on the circular drainage wall model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the combination concept of two types of piles also applies to the single pile to form the composite pile, which can exploit both merits. The precast concrete pile reinforced with cement-treated soil (PCCS) is a novel type of composite pile, which is created by driving the PC pile, termed inner core, into the DM column, termed outer core [18][19][20][21]. In order to increase the pile spacing and give full play to the economic merits of the PCCS, a novel CCF reinforced by penetrated PCCSs and floating DM columns is proposed and utilized to improve soft soils.…”
Section: Introductionmentioning
confidence: 99%
“…The bearing performances of the PCCS were investigated by means of experimental, theoretical, and numerical analysis under vertical and lateral loads [26][27][28][29][30][31]. The inner core is installed to bear external loads, while the outer core can increase the shaft friction of the inner core and effectively transfer the inner core's axial force to the surrounding soil [18]. The PCCS can reduce costs by nearly 30% under the same bearing capacity provided by the PCCS and the piles with the same geometric dimensioning [32].…”
Section: Introductionmentioning
confidence: 99%